Blood flow analysis inside different arteries using non-Newtonian Sisko model for application in biomedical engineering. (July 2020) - Toghraie, Davood; Esfahani, Navid Nasajpour; Zarringhalam, Majid; Shirani, Nima; Rostami, Sara
Highlights: Simulation of blood flow is carried out inside the artery. Different constant heat fluxes are applied on the walls of the artery. Results are reported in axial and radial directions. Blood temperature is increased with increasing axial distance. Maximum temperatures are seen at maximum axial and radial distances from entry. Abstract: Background and Objective: In the present research, simulation of blood flow is carried out inside the artery with different radiuses of 0.002 m, 0.0025 m, 0.003 m, and 0.0035 m. Methods: To simulate the blood as non-Newtonian fluid using of Sisko model, different constant heat fluxes are applied on the boundary walls of the artery. Then, the results of velocity, temperature, and Nusselt number are reported versus axial and radial directions. Results: Results show that blood temperature is enhanced with increasing axial distance. Also, maximum temperatures are seen at maximum axial and radial distances from references of entry and central regions of artery. Furthermore, increasing the radius of the artery can increase blood temperature due to a reduction in blood velocity inside the vessel. Consequently, blood particles can spend more time to receive thermal energy, which leads to emerging higher blood temperature. This phenomenon can be important in the oxygenation process inside the human body. It is observed that effect of increasing the radius of the artery can enhance blood temperature as much as 0.001 K. Also, applying constant heat fluxes in order 4 W/m 2 to 5 W/m 2 and 6 W/m 2 on the artery wall brings axial Nusselt values of 0.365–0.4575 and 0.55, respectively. As a result of axial and radial Nusselt numbers, it is reported that because radial Nusslet is unchanged in the central region of the artery, temperature shall be constant in a radius less of 0.0019 m. Therefore, the influences of heat fluxes are ignorable in the central region of the vein. Also, maximum temperatures are reported as much as 310.5 K, 311.1 K, and 311.5 K in order of applying thermal boundary flux of q'' = 400 W/m 2, q'' = 800 W/m 2 and q'' = 1000 W/m 2 respectively. Therefore, applying heat fluxes in the range of investigated can raise the blood temperature as much as 1.5 °C, which is equal to 38.5 °C. Thus, there is no doubt that such a high temperature is dangerous for human health. Conclusions: As conclusion, the results of this research are important hints for medical diagnostics of oxygenation, hematocrit, polycythemia, and blood disorders.